2002
DOI: 10.1007/s100380200006
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphism in the promoter region of the gelatinase B gene in relation to coronary artery disease and restenosis after percutaneous coronary intervention

Abstract: The matrix metalloproteinases appear to play an important role in the development and progression of atherosclerotic lesions. We studied the C-1562T polymorphism of the gelatinase B promoter in relation to coronary artery disease and restenosis after a percutaneous coronary intervention (PCI) in Koreans. To determine the frequency of the C-1562T allele, we examined 63 patients with coronary artery disease who underwent both PCI and 6-month follow-up coronary angiograms (CAGs), and 67 control patients with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 11 publications
(17 reference statements)
2
23
0
Order By: Relevance
“…However, when the studies of Cho et al [30] and Horne et al [7] were excluded, the Egger test did not suggest the presence of a publication bias (p = 0.1696) (online suppl. fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the studies of Cho et al [30] and Horne et al [7] were excluded, the Egger test did not suggest the presence of a publication bias (p = 0.1696) (online suppl. fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the –1562C/T polymorphism, according to the inclusion criteria, a total of 14 studies from 14 articles were identified [3,4,5,7,8,13,20,22,23,30,31,32,33,34]. A list of the relevant details abstracted from these studies was provided (online suppl.…”
Section: Resultsmentioning
confidence: 99%
“…1). Finally, 16 papers (Pollanen et al, 2001;Wang J. et al, 2001;Cho et al, 2002;Kim et al, 2002;Morgan et al, 2003;Haberbosch and Gardemann, 2005;Nuzzo et al, 2006;Horne et al, 2007;Nanni et al, 2007;Koh et al, 2008;Alp et al, 2009;Fallah et al, 2010;Ghaderian et al, 2010;Zhi et al, 2010;Opstad et al, 2012;Wang L. et al, 2012) were included in our meta-analysis involving 11 032 CAD patients and 4628 non-CAD controls. We divided the included studies into three sections according to ethnicities: Western populations, East Asians, and West Asians.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The MMP-9 gene has three major polymorphisms in the promoter, coding and untranslated regions (Zhang et al, 1999b). Of these, the C1562T (rs3918242) polymorphism (C→T) in the promoter region is of special interest, for many studies have found a close association between C1562T polymorphism and CAD (Cho et al, 2002;Morgan et al, 2003;Koh et al, 2008;Zhi et al, 2010). However, some other studies (Haberbosch and Gardemann, 2005;Alp et al, 2009) did not found such a close relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this variant was extensively and repeatedly studied in CAD. Both positive [120,121] and negative [122,123] association of −1562T allele with the disease were presented. The metaanalysis of previous studies showed no association of MMP-9-1562 C/T polymorphism with coronary heart disease [113].…”
Section: Mmp-9mentioning
confidence: 99%